An Investigation of Five Types of Personality Trait Continuity: A Two-Wave Longitudinal Study of Spanish Adolescents from Age 12 to Age 15 - Ibáñez, Manuel I.; Viruela, Ana M.; Mezquita, Laura; Moya, Jorge; Villa, Helena; Camacho, Laura; Ortet, Generós (Frontiers in Psychology, 2016)
The present study investigated five types of personality trait continuity using two measurement waves of Spanish adolescents (N = 234). Personality traits were measured with the short form of the Junior Spanish NEO-PI-R (JS NEO-S) at ages 12 and 15. The results showed stability in the personality trait structure, as well as decreases in the mean levels of agreeableness and conscientiousness. The results also showed moderate rank-order consistency. Individual-level changes were more pronounced for neuroticism and conscientiousness. Approximately 90% of the participants showed ipsative consistency. The findings showed some personality trait changes occurred from age 12 to age 15, but the changes were less marked than expected during this period of biological and social development. Our results also support the disruption hypothesis, as we found dips in conscientiousness and, to a lesser degree, agreeableness.